Dampak Penggunaan Gadget Bagi Perkembangan Peserta Didik Di SMPN 1 Bantan - Ramadhan, Firly; Istiqomah , Nur (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
This study aims to determine and understand the impact of using gadgets on the development of students' behavior at SMPN 1 Bantan. The method used in this study is a qualitative method. The results of the study show that the use of gadgets greatly impacts the development of student behavior, both positive and negative impacts depending on how a student uses the gadget, if the use of the gadget is good then it will also have a good impact on the development of behavior, otherwise if the gadget is used unwisely then will have a negative impact on the development of student behavior at SMPN 1 Bantan. Children must also be able to use gadgets if they are to be used in the future, because following technological advances is one of the adaptive functions of humans. Gadgets are sophisticated media that can be interpreted as vital goods/instruments, which can be used for all daily needs, as with other electronic equipment, a tool is a container with two sides, when used properly it will provide benefits for both parties. Good for adults and children